Um Estudo Etnobotânico da Conexão Homem/Cactaceae no Semi-árido baiano - Andrade, Cassia Tatiana da Silva (2002)
The use of cacti is one of the most important connexions between humans and plants in the dryland region of Brazil, where they are used as food, medicines and in horticulture amongst many other purposes. There is very little knowledge of this connexion available in a systematically and synthetic form at the moment. Therefore the present study aims to evaluate the literature by using a field study in five municipios in the state of Bahia: Valente, Queimadas, Santaluz, São Domingos and Canudos. Informal and semi-structured interviews were carried out with 32 local people. The interviews were tape-recorded and transcribed verbatim. The sample was defined after meeting the possible interviewees ad libitum, causing the increase of information to flow in a 'snow-ball' progression. This method allowed us to reach a level of exhaustive sampling through progressive inclusion of information. The material was herborized, determined by specialists and included in the collection at HUEFS herbarium. The ten species identified as used locally by the 'informants' were determined as: Cereus jamacaru DC., Harrisia adscendens (Guerke) Britton & Rose, Melocactus salvadorensis Werdermann, Nopalea cochenillifera (L.) Salm-Dyck, Opuntia dillenii (Ker-Gawler) Haworth, Opuntia ficus-indica (L.) Miller Opuntia palmadora Britton & Rose, Pilosocereus catingicola (Guerke) Byles & Rowley, Pilosocereus gounellei (Weber) Byles & Rowley, Pilosocereus tuberculatus (Werdermann) Byles & Rowley. The analysis of the diverse uses allowed us to include them in eight of the connexive types proposed by Marques: ludic, medical, mystic, economic, esthetic, domestic, erotic and trophic. The medical and trophic connections can be subdivided into direct and indirect sub-types. The use categories with largest number of species were trophic indirect [N= 10] and direct [N= 6], and medical direct [N= 7]. Connexions with strong, permanent status were present [e.g. use as hedges - connexion of domestic type; as ornamental plants - connexion of esthetic type; commercialization - economic connexion; 'white sourcery' - mystic type; as medicine - medical type] as weak, residual ones [domestic connexion related to manufacture of doors, windows and other parts of the house]. Some of the data obtained through this research agree with information found in literature, however, many of the uses registered here are original, and point towards new perspectives for the evaluation of the adaptations of the rural population in the Brazilian drylands.